Prudence's Impact On The Quality Of Financial Reports When It Comes To Reducing Financial Activities - Riyanto Setiawan Suharsono; Moh. Halim; Justita Dura (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: The research aims to analyze prudence in reducing financial distress on the quality of company financial reports in Indonesia. Methodology/approach: The population in this research is all companies listed on the Indonesian Stock Exchange. Based on the results of sample calculations using G*power, the minimum sample size is 472 respondents, so the researchers used 500 companies using the proportional random sampling method. The data analysis method used in this research is the Structural Equation Model (SEM). Findings: Financial distress has a positive effect on prudence. Financial distress has a positive impact on the quality of financial reports. Prudence has a positive effect on the quality of financial reports. Financial distress has a positive impact on the quality of financial reports through prudence. Practical implications: The practical implication of this research is that by understanding and applying the principle of prudence in financial reporting, companies in Indonesia can reduce the risk of financial distress and improve the quality of their financial reports, which will support more stable and sustainable economic growth. Originality/value: Prudence is an intervening variable because prudence is a measure of company profits in one period so it will impact the quality of financial reports.